2014
DOI: 10.1021/la4047275
|View full text |Cite
|
Sign up to set email alerts
|

Critical Salt Effects in the Swelling Behavior of a Weak Polybasic Brush

Abstract: The swelling behavior of poly(2-(diethylamino)ethyl methacrylate) (PDEA) brushes in response to changes in solution pH and ionic strength has been investigated. The brushes were synthesized by ARGET ATRP methodology at the silica-aqueous solution interface via two different surface-bound initiator approaches: electrostatically adsorbed cationic macroinitiator and covalently anchored silane-based ATRP initiator moieties. The pH-response of these brushes is studied as a function of the solvated brush thickness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
118
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(134 citation statements)
references
References 52 publications
14
118
2
Order By: Relevance
“…7) 22,23 , which predicts that the brush should collapse with increasing salt concentration (C), but only as a relatively weak power law (C À 1/3 ). We see a comparatively steeper ionic strength-dependence, which has been previously observed in synthetic polymer systems [24][25][26][27][28][29] and may arise from the local modulation of protein charge-based interactions due to added salt. At pH 10.9, below a critical ionic strength (B2 mM), the system enters an 'osmotic brush' regime in which the brush height increases with ionic strength.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…7) 22,23 , which predicts that the brush should collapse with increasing salt concentration (C), but only as a relatively weak power law (C À 1/3 ). We see a comparatively steeper ionic strength-dependence, which has been previously observed in synthetic polymer systems [24][25][26][27][28][29] and may arise from the local modulation of protein charge-based interactions due to added salt. At pH 10.9, below a critical ionic strength (B2 mM), the system enters an 'osmotic brush' regime in which the brush height increases with ionic strength.…”
Section: Resultssupporting
confidence: 67%
“…As a consequence, the pH within the brush increases, thereby increasing the degree of deprotonation of the protein chains. This results in greater chain stretching due to counterion-induced osmotic swelling and increased inter-and intra-molecular electrostatic repulsion associated with chain ionization, as has been observed with synthetic polyelectrolyte and polyampholyte brush systems 24,28,29 . Above a critical ionic strength, this exchange mechanism saturates and the system enters the 'salted brush' regime, in which further addition of salt collapses the brush due to electrostatic screening ( Supplementary Figs 6 and 7).…”
Section: Resultsmentioning
confidence: 79%
“…Taking the NaPSS brush with more polymer chains ( σ =0.15 chain nm −2 ) as an example, the time for the brushes to recover to their initial state (the state under salt‐free conditions) was about seven times longer than the process of swelling enhancement. This difference is very similar to what was observed in the weak polyelectrolyte brushes systems, although its physical mechanism differs from the current permanently charged system. Secondly, the kinetics of de‐enhancement depend on the grafting density: The brushes with lower grafting densities recovered much faster than the brushes with higher grafting densities.…”
Section: Resultssupporting
confidence: 84%
“…28 Our previous work has shown that the ideal dry thickness for the brushes to be investigated by ellipsometry is ~20 nm. 26,28,30 Polymerization times were selected accordingly and measured brush thickness values are given in Table 1. For the QCM-D measurements similar dry thickness brushes were used for poly(DEA) and poly(DPA).…”
Section: Surface Initiator-functionalization and Brush Polymerizationmentioning
confidence: 99%
“…Several publications have experimentally investigated the effects of salt on a weak polyelectrolyte brush in order to compare with theoretical scaling laws. 28,53,54,55,56,57 Significantly, three of these studies report weaker scaling exponents for brush thickness with increasing ionic strength for the salted brush regime. 28,55,57 Furthermore, our previous work on a poly(2-diethylamino)ethyl methacrylate brush showed that in the osmotic brush regime the brush transitions from a collapsed to swollen conformation over a much narrower concentration range than predicted theoretically.…”
Section: Introductionmentioning
confidence: 98%